The Magmatic Gas Signature of Pacaya Volcano, With Implications for the Volcanic CO2 Flux From Guatemala. (10th March 2018) - Battaglia, A.; Bitetto, M.; Aiuppa, A.; Rizzo, A.L.; Chigna, G.; Watson, I. M.; D'Aleo, R.; Juárez Cacao, F. J.; de Moor, M. J.
Abstract: Pacaya volcano in Guatemala is one of the most active volcanoes of the Central American Volcanic Arc (CAVA). However, its magmatic gas signature and volatile output have received little attention to date. Here, we present novel volcanic gas information from in‐situ (Multi‐GAS) and remote (UV camera) plume observations in January 2016. We find in‐plume H2 O/SO2 and CO2 /SO2 ratios of 2‐20 and 0.6‐10.5, and an end‐member magmatic gas signature of 80.5 mol. % H2 O, 10.4 mol. % CO2, and 9.0 mol. % SO2 . The SO2 flux is evaluated at 885 ± 550 tons/d. This, combined with co‐acquired volcanic plume composition, leads to H2 O and CO2 fluxes of 2, 230 ± 1, 390 and 700 ± 440, and a total volatile flux of ∼3, 800 tons/d. We use these results in tandem with previous SO2 flux budgets for Fuego and Santiaguito to estimate the total volcanic CO2 flux from Guatemala at ∼1, 160 ± 600 tons/day. This calculation is based upon CO2 /total S (St ) ratios for Fuego (1.5 ± 0.75) and Santiaguito (1.4 ± 0.75) inferred from a gas (CO2 /St ratio) versus trace‐element (Ba/La ratio) CAVA relationship. The H2 O‐poor and low CO2 /St ratio (∼1.0‐1.5) signature of Pacaya gas suggests dominant mantle‐wedge derivation of the emitted volatiles. This is consistent with 3 He/ 4 He ratios in olivine hosted fluid inclusions (FIs), which range between 8.4 and 9.0 Ra (being Ra the atmospheric 3 He/ 4 He ratio) at the upper limit of MORB range (8 ± 1 Ra). These values are the highest ever measured in CAVA and among the highest ever recorded in arc volcanoes worldwide, indicating negligible 4 He contributions from the crust/slab. Key Points: We present the first volcanic gas compositional time‐series and noble gas compositions of olivine‐hosted FIs from Pacaya (Guatemala) We identify the magmatic gas signature and the Total Volatile Flux budget for one of the most active CAVA volcanoes for the first time Our results contribute novel information on the total volcanic CO2 budget from Guatemalan volcanoes